Profile of Hypospadias Cases in Central Java, Indonesia - Ziske Maritska; Ardy Santosa; Mahayu Dewi Ariani; Achmad Zulfa Juniarto; Sultana MH Faradz (Faculty of Medicine, Diponegoro University, 2015)
Background: Hypospadia is believed to be a multifactorial disease. The risk factors that may induce the formation of hypospadias are environmental factors, endocrine disruptors, and genetic factors. The aim of this study was to describe the profile of hypospadias patients who visited the Center for Biomedical Research (CEBIOR), Faculty of Medicine, Diponegoro University, Semarang, Indonesia.Methods: This study is an observational study, using patients’ medical record in CEBIOR from 2010 to 2012. The hypospadias cases were classified into syndromic, isolated and severe hypospadias based on their phenotype. The history of pregnancy, birth characteristics, and family history of the patients were described.Results: There were 120 cases of hypospadias, consisted of 48.33% severe hypospadias, 41.67% mild isolated hypospadias and 10% syndromic hypospadias. There were 38.33% hypospadias cases whose mothers were being exposed to repellant usage and 39.17% cases whose fathers were smoking. Forty (33.33%) probands’ mothers were aged above 35 years old when they gave birth to their affected son.Conclusion: Majority of hypospadias cases were severe and mild isolated. Environtmental factors including maternal age more than 35 years old, use of repellant, and smoking fathers were found in this study.